Building the taxonomic profile of the Riniaie Marwah hot spring of Kishtwar in Jammu and Kashmir: the first high-throughput sequencing-based metagenome study - Wani, Atif Khurshid; Ahmad, Suhail; Americo-Pinheiro, Juliana Heloisa Pine [UNESP]; Tizro, Nazli; Singh, Reena (Univ Medical Sciences-danishgah-i Ulum-i Pizishki-i Tihran, 2023)
Background and Objectives: Rinaie Marwah hot spring Kishtwar (RMHSK) is one of the geothermal springs located at 33 degrees 51 ' 51 '' N 75 degrees 32 ' 07 '' E with an elevation of 2134 meters above sea level in Jammu and Kashmir, India. We aimed to study the microbial diversity of this geothermal spring using metagenomics.Materials and Methods: In the present study, physiochemical parameters including temperature (65-75oC), pH (6. 9-8. 8), hardness (250 ppm), and mineral content was measured along with the microbial diversity using Illumina MiSeq metage-nome-based 16s amplicon sequencing (V3-V4). The sequence reads were classified taxonomically into 31 phyla, 71 classes, 152 orders, 256 families, 410 genus, and 665 species. QIIME 2 (Quantitative Insights into Microbial Ecology), an extensible, powerful, and decentralized analytical tool, was used for taxonomic analysis.Results: Bacteroidota (32. 57%) was the dominant phylum, Bacteroidia (32. 51%) the dominant class, Bacteroidales (16. 6%) the dominant order, and Lentimicrobiaceae (14. 23%) was the dominant family per the abundance analysis. Shannon (2. 28) and Chao 1 (87. 0) diversity indices support the existence of higher microbial diversity in RMHSK (50717 OTUs).Conclusion: The microbial diversity of RMHSK is reported for the first time through a metagenomic study. Identification of microorganisms with characteristics that are relevant to industries.
Keywords: Hot spring; Metagenome; Taxonomy; High throughput DNA sequencing; Illumina sequencing